Wideband Continuous-time ΣΔ ADCs, Automotive Electronics, and Power Management Advances in Analog Circuit Design 2016 - Baschirotto, Andrea; Harpe, Pieter; Makinwa, Kofi A. A. (Springer International Publishing : Imprint: Springer, 2017)
This book is based on the 18 tutorials presented during the 25th workshop on Advances in Analog Circuit Design. Expert designers present readers with information about a variety of topics at the frontier of analog circuit design, including low-power and energy-efficient analog electronics, with specific contributions focusing on the design of continuous-time sigma-delta modulators, automotive electronics, and power management. This book serves as a valuable reference to the state-of-the-art, for anyone involved in analog circuit research and development.